Czechoslovak Mathematical Journal - Fiedler, Miroslav; Englis, Miroslav; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Czechoslovak Mathematical Journal, publishes original research papers in mathematics.
Keywords: Mathematics; Mathematical analysis; Analysis (Mathematics).; Differential equations; Mathematical models; Convex geometry; Discrete geometry; Mathematics, general; Analysis; Convex and Discrete Geometry; Ordinary Differential Equations; Mathematical Modeling and Industrial Mathematics